2006
DOI: 10.1021/jf0531959
|View full text |Cite
|
Sign up to set email alerts
|

Absorption of Anthocyanins from Blueberry Extracts by Caco-2 Human Intestinal Cell Monolayers

Abstract: Recent studies have shown that dietary polyphenols may contribute to the prevention of cardiovascular disease and cancer. Anthocyanins from different plant sources including blueberries have been shown to possess potential anticancer activities. One of the key factors needed to correctly relate the in vitro study results to human disease outcomes is information about bioavailability. The objectives of the current study were to evaluate the absorption of blueberry anthocyanin extracts using Caco-2 human intesti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
128
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 162 publications
(135 citation statements)
references
References 48 publications
(63 reference statements)
7
128
0
Order By: Relevance
“…The most striking antioxidant activity is cyaniding 3-galactose. DPPH assays showed that it was more effevtive than flavonol glycoside and the standards in scavenging free radicals, with an EC50 of 7.7 M compared to 17.3 M for myricetin 3-arabinoside and 30 M for trolox standard [4,130,131] Increased plasma antioxidant status, protected RBC against hemolysis [126,132] Showed protective effects on PC12 cells damage and chronic diseases associated with oxidative stress [133] Showed neuro and mitochondrio-protective effect [134] Antioxidant Activities Showed antioxidative activity under the used assay conditions towards prevention of oxidative DNA damage [135] Inhibited proliferation of MCF-7, MDA-MB-231 and MDA-MB-435 breast cancer cells [4,8,126,127] Inhibited the induction of ornithine decarboxylase, an enzyme involved in tumor proliferation, and induce quinine reductase, an enzyme that can inactivate certain carcinogens [136] Exhibited the human colon tumor cell lines Caco-2, HT-116, and HT-29 [10,137,138] Exhibited the anticancer effects on DLD-1 and COLO205 cells [139] Inhibited matrix metalloproteinase activity in DU145 human prostate cancer cells [140] Exhibition of anticancer capability in human lung and leukemia cells [105] Modulated the expression of cyclooxygenase-2 (COX-2) and I B in human colon cancer cells [141] Cytotoxicities Inhibitory effect on activator protein-1, nuclear factor-B, and mitogen-activated protein kinases activation [105,142] Prevented the urinary tract infections [143] Showed potential inhibitory effect against bacteria involved in dental caries and periodontal diseases [147,148] Exhibited potent biological activity by inhibiting adherence of uropathogenic isolates of P-fimbriated Escherichia coli bacteria to cellular surfaces containing -Gal(1 4)--Gal receptor sequences similar to those on epithelial cells in the urinary tract [149,150] Antimicrobial Activities…”
Section: Biosynthesis Pathways Of Anthocyanins and Flavonoids (Fig 3mentioning
confidence: 99%
“…The most striking antioxidant activity is cyaniding 3-galactose. DPPH assays showed that it was more effevtive than flavonol glycoside and the standards in scavenging free radicals, with an EC50 of 7.7 M compared to 17.3 M for myricetin 3-arabinoside and 30 M for trolox standard [4,130,131] Increased plasma antioxidant status, protected RBC against hemolysis [126,132] Showed protective effects on PC12 cells damage and chronic diseases associated with oxidative stress [133] Showed neuro and mitochondrio-protective effect [134] Antioxidant Activities Showed antioxidative activity under the used assay conditions towards prevention of oxidative DNA damage [135] Inhibited proliferation of MCF-7, MDA-MB-231 and MDA-MB-435 breast cancer cells [4,8,126,127] Inhibited the induction of ornithine decarboxylase, an enzyme involved in tumor proliferation, and induce quinine reductase, an enzyme that can inactivate certain carcinogens [136] Exhibited the human colon tumor cell lines Caco-2, HT-116, and HT-29 [10,137,138] Exhibited the anticancer effects on DLD-1 and COLO205 cells [139] Inhibited matrix metalloproteinase activity in DU145 human prostate cancer cells [140] Exhibition of anticancer capability in human lung and leukemia cells [105] Modulated the expression of cyclooxygenase-2 (COX-2) and I B in human colon cancer cells [141] Cytotoxicities Inhibitory effect on activator protein-1, nuclear factor-B, and mitogen-activated protein kinases activation [105,142] Prevented the urinary tract infections [143] Showed potential inhibitory effect against bacteria involved in dental caries and periodontal diseases [147,148] Exhibited potent biological activity by inhibiting adherence of uropathogenic isolates of P-fimbriated Escherichia coli bacteria to cellular surfaces containing -Gal(1 4)--Gal receptor sequences similar to those on epithelial cells in the urinary tract [149,150] Antimicrobial Activities…”
Section: Biosynthesis Pathways Of Anthocyanins and Flavonoids (Fig 3mentioning
confidence: 99%
“…Results of in vitro digestion models are often different from those of in vivo models as it is difficult to accurately simulate the complex physiological events taking place in living organisms (Hur, Lim, Decker, & McClements, 2011). Because in vitro studies offer advantages such as simplicity, ease of application and low cost to the investigator, they are preferred than in vivo studies (Yi, Akoh, Fischer, & Krewer, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…The samples were frozen until used for the HPLC analysis. The transport efficiency is given as a percentage, calculated according to: (the compound concentrations on the basolateral side at a given time)/(compound concentrations on the apical side at the zero hour)*100, as in [15].…”
Section: Transport Studiesmentioning
confidence: 99%